2006
DOI: 10.1002/anie.200602773
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Cross‐Coupling Reactions of Diazine N‐Oxides with Aryl Chlorides, Bromides, and Iodides

Abstract: New aspects of N‐oxides: Pyrazine, pyridazine, and pyrimidine N‐oxides are regioselectively arylated with aryl iodides, bromides, and chlorides in the presence of a palladium catalyst (see scheme). The resulting products can be deoxygenated in high yield or further functionalized by making use of the N‐oxide functionality. FG=functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(76 citation statements)
references
References 18 publications
3
72
0
1
Order By: Relevance
“…[24] Their oxidizing character parallels that of amine N-oxides. [25] Significantly, Zhang and co-workers developed the intermolecular version of oxygen-atom transfer reactions between terminal alkynes and halopyridine Noxides.…”
Section: Oxygen-atom Transfer From Pyridine N-oxidesmentioning
confidence: 97%
“…[24] Their oxidizing character parallels that of amine N-oxides. [25] Significantly, Zhang and co-workers developed the intermolecular version of oxygen-atom transfer reactions between terminal alkynes and halopyridine Noxides.…”
Section: Oxygen-atom Transfer From Pyridine N-oxidesmentioning
confidence: 97%
“…随后相继报道了吡嗪、哒嗪、嘧啶等二嗪氮氧化物 和卤代芳烃的 C-H 键活化交叉偶联反应 [43] , 反应中需 [44] . 以 Pd 2 (dba) 3 为钯试剂, X-Phos 为配体, NaOBu-t 为碱, 甲苯 为溶剂, 实现了吡啶苄基上的 sp 3 -C-H 键的芳基化 [45] .…”
Section: Scheme 13unclassified
“…82 Later, Fagnou extended this methodology for functionalization of diazine N-oxides series (Scheme 54). 83 Direct arylation of pyrazine-148, pyridazine-149, and pyrimidinecontaining 150 substrates was performed with a wide range of both electron-rich and electron-deficient aryl-iodides, -bromides and -chlorides. It was also found that addition of catalytic amounts of Cu(I) salts enhances reactivity of low-reactive substrates like pyrimidine N-oxides 150.…”
Section: C-h Arylation Of Electron-deficient Heterocyclic Systemsmentioning
confidence: 99%
“…This method allows the construction of 5/5 or 5/6 fused, as well as 5/5-spiro skeletons (Scheme 61). 83 Further, Beccalli developed a protocol for the intramolecular regioselective cyclization of indole carboxamide derivatives 180 into β-carbolinones 182 or pyrazino[1,2-a]indoles 181 (Scheme 62). 94,95 It was found that the regiochemistry can be completely controlled by the reaction conditions to allow for either C-H or N-H functionalization selectively or exclusively.…”
Section: Reactions Involving C-c Bond Formationmentioning
confidence: 99%